Pomen terenskega dela za bodoče učitelje razrednega pouka - Korošec, Urška (Revija za elementarno izobraževanje, 2009)
The article presents the results of research conducted on a sample of first year students from the Faculty of Education, University of Maribor. The purpose of the study was to find out whether there are differences among students when identifying plants and animals, applying collecting methods for living organisms and the impact of factors such as: stratum of the finished education, vicinity of natural environments in the home neighbourhood, and previous experiences with biological activities. In addition, we assessed the influence of field activities outside the classroom: identification of plants, animals, and applications of collecting methods for living organisms. We found that all three factors influenced the identification of plants and animals, thus in-creasing student knowledge. The students who attend activities outside the classroom obtain better results; this finally confirms the importance of field experience.
Keywords: vzgoja in izobraževanje; naravoslovje; razredni pouk; terensko delo; transmisija; constructivism; konstruktivizem; organizacija pouka; metodika; učne metode